Comparative study between assisted laparoscopic and open D2 distal gastrectomy for gastric cancer - Amer, Naglaa Fathy; El Shakhs, Soliman Abdelrahman; Mohamed, Moharam Abdelsamie; Shahin, Mahmoud (International Surgery Journal, 2019)
Background: Although laparoscopic gastrectomy has been in use for many years, there was great debate for its technical feasibility and oncological safety. However, with recent advancements of laparoscopic surgical instruments and the accumulation of operative experience, laparoscopic gastrectomy becomes more feasible, and laparoscopic D2 lymphadenectomy has been achieved. Methods: This study was prospectively conducted from April 2016 to September 2018 on 40 patients presenting with distal gastric cancer to the outpatient clinic of Menoufia University Hospitals. All patients in the study performed radical distal gastrectomy with D2 lymphadenectomy aiming for cure. The patients were divided into 2 groups: group A (20 patients operated upon with open gastrectomy (OG) technique) and group B (20 patients operated upon with the laparoscopic gastrectomy (LG) technique). Both groups were compared in this study regarding operative details, short term post-operative complications and pathological results. Results: The mean operative time in OG was shorter than LG (p value: 0.04), while there was significant difference between both groups regarding blood loss, mean blood loss in OG was 420.8±87.6 ml and in LG was 283.4±45.9ml, parenteral analgesic requirement was significantly less in LG than OG (p value: 0.04) while no significant difference regarding Intra-operative complications and pathological results. Conclusions: Assisted Laparoscopic distal gastrectomy with D2 lymphadenectomy is feasible and safe with less post-operative pain and short hospital stay.